МАТЕРИАЛЫ К ФАУНЕ ПОЛУЖЕСТКОКРЫЛЫХ (HETEROPTERA) ПРИРОДНОГО ПАРКА «К0ЛСАЙ К0ЛДЕРІ» (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The article presents the materials of the fauna of Heteroptera of national park "Kolsay kolderi". As a result of the studies identified 47 species of 10 families. In the zoogeographically predominantly transpalaearctics (25), holarctics (9), westpalaearctics and transeurasians (4) species.